Predictive value of "Marsh 1" type histology in subjects with suspected cealic disease. (July 2014) - Tortora, Raffaella; Capone, Pietro; Imperatore, Nicola; De Stefano, Giuliano; Gerbino, Nicolò; Leo, Maria; Caporaso, Nicola; Rispo, Antonio
Abstract Introduction. The diagnosis of celiac disease (CD) is based on histology in combination with anti-tissue transglutaminase (a-tTG) and anti-endomysial antibodies (EMAs). The increase of intraepithelial lymphocytes defines the Marsh 1 histology that appears not to be specific for CD. Aim: To explore the positive predictive value (PPV) and clinical relevance of Marsh 1 histology in suspected CD. Methods. We carried out an observational prospective study including all consecutive subjects with a Marsh 1 histology. All patients were tested for a-tTG and EMAs. Diagnosis of potential CD was defined in the presence of Marsh 1 with positive a-tTG and EMAs. Patients were investigated for symptoms, CD familial aggregation, other diseases, and current medication. Results. Sixty-three patients with Marsh 1 were included. Diagnosis of potential CD was made in 23 subjects (36%), so that Marsh 1 histology showed a PPV of 36%. With regard to familial aggregation, patients with potential CD showed a higher frequency of familiarity for CD (60.8% vs. 15.0%; p < 0.01). No significant difference was detected between CD and non-CD in terms of intestinal and extra-intestinal symptoms. We also documented the presence of conditions other than CD in the remaining population: 7 patients (17.5%) with immuno-mediated diseases while 5 patients (12.5%) showed Helicobacter pylori (HP) infection. About medication, 3 patients (7.5%) were on non-steroidal anti-inflammatory drugs, while another 4 (10%) patients were being treated with other drugs. Conclusion. The Marsh 1 type histology is not specific for CD and it can also be associated with immuno-mediated disorders, HP infection, and drugs.